Measuring exposure to second-hand smoke in the home and car : UK, Ireland and Malaysia. - Semple, Sean; Zainal Abidin, Emilia (International Union Against Tuberculosis and Lung Disease, 2013)
Background: Second-hand smoke(SHS)exposure in the private spaces of home and cars continues to be common even in countries with comprehensive smoke-free laws. There is little data available on the concentrations of SHS experienced within these micro-environment.